ASSESSING THE PRISMA POTENTIAL FOR MINERAL EXPLORATION TO VECTOR LOW-GRADE LITHIUM DEPOSITS - Cardoso Fernandes, J (2022)
PRISMA data is still underexploited in what concerns mineral exploration, while the high demand for battery components such as lithium (Li) instigates exploration of other low-grade deposits such as St. Austell (Cornwall, UK). This study assesses the potential of PRISMA data to target such Li deposits through the detection of topaz as a proxy to the mineralization using band math and partial unmixing techniques. The topaz distribution maps obtained are coherent between each other and with the known geology of the area, highlighting the PRISMA potential, although there could be some shortcomings related to its spatial resolution. Comparison with Sentinel-2 or Worldview-3 data shows the limitations of multispectral products, despite some potential to use Worldview-3 that need to be further investigated. In the future, new approaches to directly detect Li-micas and field validation of the results must be conducted.